The Effect of Loan To Deposit Ratio (LDR) and Third Party Funds on Return On Equity (ROE) at PT Bank Rakyat Indonesia (Persero) Tbk Between 2012 and 2021 - Andrean Mahesta (Indonesian Financial Review, 2022)
A bank is a financial institution that functions as an intermediary by receiving deposits of money from the judiciary community to channel it back to the community in the form of credit. This study aims to determine how much influence the Loan to Deposit Ratio (LDR) and Third Party Funds have on Return On Equity (ROE). This research was conducted at PT. Bank Rakyat Indonesia (Persero) Tbk for the period 2012-2021. The method of data collection in this study is by downloading financial statements on the PT. Bank Rakyat Indonesia. The data analysis method used in this study used normality test analysis and multiple linear regression analysis. The tests that have been carried out in this study provide results that the Loan to Deposit Ratio has no effect on Return On Equity while Third Party Funds have an effect on Return On Equity.